Local urban governments financing a comparison between countries - Aghon, Gabriel; Letelier, Leonardo (Estudios de Economía, 2016)
This paper is intended to analyze, in a comparative perspective, the financing mechanisms of urban local governments in two groups of countries. The first group refers to a sample of OECD countries. They are rather decentralized, and have institutional features which date back many years from now. The scope of responsibilities faced by these countries. The second group is constituted by a number of Latin American countries. They are, in general, less decentralized and have the characteristic of not having a well established institutional structure. This has experienced various changes over the recent years, one of them being a process of transferring responsibilities to local tiers of governments, a tendency which in general, has not been accompanied by an increasing capacity to get resources neither from the central government nor from the local financial market.